Orbital complications of acute rhinosinusitis in children: Case study - Ljiljana Krsmanović; Vladimir Turuntaš; Siniša Šolaja (Биомедицинска истраживања, 2020)
Introduction: Acute rhinosinusitis (ARS) encompasses a heterogeneous group of inflammatory disorders affecting nasal mucosa and paranasal sinuses. Rhinosinusitis is the most common condition in the United States. It is estimated that over 30 million people annually visit the doctor due to this condition, while every sixth adult suffers from ARS. Among all ARS complications, over 91% are orbital complications (OC) with an average prevalence of 6% and a higher incidence in children compared to adults. Case report. Twelve-year-old boy, accompanied by his mother, was urgently referred to the Department of Otorhinolaryngology at the University Hospital in Foca due to a sudden red and painful left periorbital edema, pain in the left eye and a fever reaching 38.5ºC. After laboratory and CT scan diagnostics, an ophthalmologic examination and inpatient clinical findings after 36 hours of parenteral triple antibiotic therapy, the patient was referred to a tertiary-type institution for further treatment. The same procedure was performed conservatively during the hospitalization within 6 days. Conclusion: The initial treatment of orbital complications in children is conservative. Treatment should be started empirically, using triple antibiotic therapy. The choice of antibiotics and treatment protocols among pediatric population have not been agreed yet. If 36-48 hours after the beginning of the conservative treatment, there is lack of the clinical response, surgical treatment is absolutely indicated, regardless of the stage of orbital complication.
Keywords: acute rhinosinusitis; orbital complications; children; treatment